(untitled) - Stay, Jesse (Hoboken, N.J., 2015)
Minecraft For Dummies is the complete guide to playing within the Minecraft world. With easy-to-follow guidance from a team of Minecraft experts, you'll develop programming and engineering skills as you build amazing creations using in-game blocks and mechanical devices. Whether you prefer the PC, console, or portable platform, this helpful guide will walk you through the process of setting up and beginning gameplay, and engage with other users from all around the globe. With this trusty guidebook in hand, you'll navigate the infinite world of Minecraft with confidence, skills, and a storehouse of expert advice.
Keywords: Minecraft (Game),Computer games,Minecraft (trò chơi),Trò chơi trên máy tính